Prospective CERAD Neuropsychological Assessment in Patients With Multiple System Atrophy - Maass, Fabian; Hermann, Peter; Varges, Daniela; Nuhn, Sabine; van Riesen, Christoph; Jamous, Ala; Focke, Niels K.; Hewitt, Manuel; Leha, Andreas; Bähr, Mathias; Zerr, Inga (Frontiers in Neurology, 2022)
The objective of the study was to characterize the pattern of cognitive dysfunction in patients with multiple system atrophy (MSA) applying a standardized neuropsychological assessment. A total of 20 patients with the diagnosis of probable or possible MSA were enrolled for neuropsychological assessment applying the CERAD plus battery. All patients were tested at baseline and 14/20 patients received additional follow-up assessments (median follow-up of 24 months). Additionally, relationship between cortical thickness values/subcortical gray matter volumes and CERAD subitems was evaluated at baseline in a subgroup of 13/20 patients. Trail Making Test (TMT) was the most sensitive CERAD item at baseline with abnormal performance (z-score < −1.28) in one or both pathological TMT items (TMT-A, TMT-B) in 60% of patients with MSA. Additionally, there was a significant inverse correlation between the volume of the left and the right accumbens area and the TMT A item after adjusting for age (left side: p = 0.0009; right side p = 0.003). Comparing both subtypes, patients with MSA-C had significant lower values in phonemic verbal fluency (p = 0.04) and a trend for lower values in semantic verbal fluency (p = 0.06) compared to MSA-P. Additionally, patients with MSA-C showed significantly worse performance in the TMT-B task (p = 0.04) and a trend for worse performance in the TMT-A task (p = 0.06). Concerning longitudinal follow-up, a significant worsening in the TMT-B (p = 0.03) can be reported in MSA. In conclusion, frontal-executive dysfunction presents the hallmark of cognitive impairment in MSA.